2003
DOI: 10.2524/jtappij.57.260
|View full text |Cite
|
Sign up to set email alerts
|

The Method and Characteristics of Synthesized Zeolite Prepared from Paper Sludge Ash

Abstract: Paper sludge ash (PS ash) discharged from Fuji area, Shizuoka prefecture reach about 160,000 tons/ year. Therefore, the development of a technique for utilizing of PS ash is essential for recycling waste materials.PS ash collected in Fuji area has little of SiO2 and much Al2O3, CaO, in comparison with the general material of the artificial zeolite (e.g. coal fly ash). PS mainly consists of calcite, talc and kaolinite, which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In zeolite synthesis, transformable phases in the ash, which are easily dissolved into alkali solution, are converted into zeolite crystal (Querol et al, 2001;Ando et al, 2003c). Therefore, many synthetic processes, such as the fusion method, the dry or molten-salt method, and addition of mineralizer, have been developed to achieve high synthesis efficiency of zeolite (Shigemoto et al, 1993;Park et al, 2000;Wu et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In zeolite synthesis, transformable phases in the ash, which are easily dissolved into alkali solution, are converted into zeolite crystal (Querol et al, 2001;Ando et al, 2003c). Therefore, many synthetic processes, such as the fusion method, the dry or molten-salt method, and addition of mineralizer, have been developed to achieve high synthesis efficiency of zeolite (Shigemoto et al, 1993;Park et al, 2000;Wu et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, many synthetic processes, such as the fusion method, the dry or molten-salt method, and addition of mineralizer, have been developed to achieve high synthesis efficiency of zeolite (Shigemoto et al, 1993;Park et al, 2000;Wu et al, 2006). It has also been suggested that SiO 2 with a high solubility in alkali solution, such as water glass or diatomite, can be added into the solution with Ca-rich ash to synthesize zeolites with high CEC (Fukui et al, 2002;Ando et al, 2003cAndo et al, , 2004Wajima et al, 2006).…”
Section: Introductionmentioning
confidence: 98%